JARINGAN INTELEKTUAL ULAMA KETURUNAN SYEKH MUHAMMAD ARSYAD AL-BANJARI - ., Rahmadi (Pascasarjana UIN ANTASARI Banjarmasin, 2010)
This paper tries to explore the intellectual network of the scholars descendant of Sheikh Muhammad Arsyad al-Banjari. As for the writer, the intellectual network is formed over two centuries, because of the tradition of learning among fellow relatives who form a relationship that not only kinship but also the teacher-student relationships. The intellectual network was then expanded through the process of rihlah ilmiyyah. The emergence of a central figure or actor among their networks, increased mobility and migration and the presence of mating with close relatives and external circles who have a persona in the field of religion.